El uso progresivo de la fuerza dentro de los centros penitenciarios para la prevención de actos violentos - Puruncajas Orozco, Paulo Sebastián (2023)
ABSTRACT: The progressive use of force is a means that seeks to maintain order in prisons, being a solution to the violent events that may occur. For this means to be effective, several parameters have been established, such as persuasion techniques, agreements, negotiation, and/or mediation, before using force. The Ecuadorian penitentiary system has presented several problems, leading to a prison crisis that needs a solution to maintain control. The main penitentiary centers have ended the lives of several inmates, either by settling scores, fighting between rival gangs, or for territorial control and drug trafficking routes, which is why it has entered the black list of countries with the highest number of murders in prison riots. Therefore, it is necessary to compare the prison situation in Ecuador with other prisons in other countries, taking into account the reality of prisons, overcrowding, and the presence of drug gangs seeking control of prisons. In the same way, analyzing the jurisprudence, doctrine, and critical analysis allows specification of the current situation of the penitentiary system and the leading causes that provoke violent acts inside the main prisons of Ecuador.